2021
DOI: 10.1016/j.nicl.2021.102613
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain structural connectivity in patients with longstanding gut inflammation is correlated with psychological symptoms and disease duration

Abstract: Highlights IBS and Ulcerative Colitis (UC) patients have changes in brain network organization. Changes in brain network organization correlate with disease symptomatology. In UC, brain network organization changes correlate with disease duration. Chronic gut inflammation as well as pain have neuroplastic effects on the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 93 publications
2
18
0
2
Order By: Relevance
“…However, this negative result is difficult to interpret given the absence of group differences in chronic stress levels in our UC cohort, indicating essentially normal perceived chronic stress in this sample despite elevated clinical symptoms of anxiety as quantified with the HADS. While sample characteristics of UC were in this respect similar to an earlier study in a different sample of UC that used a comparable recruitment strategy ( 75 ), other studies from our own group ( 76 ) and other groups [e.g., ( 63 )] reported more psychological impairment in patients, including elevated chronic stress levels. The lack of elevated chronic stress in this UC sample obviously limits the interpretation of these results, although owing to our approach to test the interaction this does not per se exclude an impact but rather a disease-specific differential association compared to controls.…”
Section: Discussionsupporting
confidence: 70%
“…However, this negative result is difficult to interpret given the absence of group differences in chronic stress levels in our UC cohort, indicating essentially normal perceived chronic stress in this sample despite elevated clinical symptoms of anxiety as quantified with the HADS. While sample characteristics of UC were in this respect similar to an earlier study in a different sample of UC that used a comparable recruitment strategy ( 75 ), other studies from our own group ( 76 ) and other groups [e.g., ( 63 )] reported more psychological impairment in patients, including elevated chronic stress levels. The lack of elevated chronic stress in this UC sample obviously limits the interpretation of these results, although owing to our approach to test the interaction this does not per se exclude an impact but rather a disease-specific differential association compared to controls.…”
Section: Discussionsupporting
confidence: 70%
“…This in turn might result in difficulties in interpersonal relationships and the development of psychological comorbidities, as well as problems in patient–physician interactions and decreased medication adherence ( Agostini et al, 2019 ; Colonnello and Agostini, 2020 ). This hypothesis is further supported by neuroimaging studies of patients with IBD, which found alterations in brain areas (e.g., the midcingulate cortex), that are involved in emotion processing ( Agostini et al, 2011 , 2013a , b , 2017 ; Vogt, 2013 ; Zikou et al, 2014 ; Kragel et al, 2018 ; Hou et al, 2019 ; Colonnello and Agostini, 2020 ; Fan et al, 2020 ; Skrobisz et al, 2020 ; Thomann et al, 2020 ; Turkiewicz et al, 2021 ; Yeung, 2021 ). This is in line with previous studies that reported that IBD patients are characterized by mentalizing deficits compared to healthy controls (HCs).…”
Section: Introductionmentioning
confidence: 72%
“…With regard to the psychological burden of anxiety and depression, the direction of (neuro-)inflammatory processes and disease activity in CD/UC seems to be bidirectional – with patients with anxiety symptoms developing more often disease flares, and patients with disease activity developing more anxiety ( Gracie et al, 2018 ). Additionally, recent neuroimaging studies have shown that patients with (active) IBD have an altered brain structure, which is associated with symptoms of depression and anxiety ( Agostini et al, 2011 , 2013a , b , 2017 ; Vogt, 2013 ; Zikou et al, 2014 ; Kragel et al, 2018 ; Hou et al, 2019 ; Colonnello and Agostini, 2020 ; Fan et al, 2020 ; Skrobisz et al, 2020 ; Thomann et al, 2020 ; Turkiewicz et al, 2021 ; Yeung, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the disorders of gutbrain interaction, altered structural covariance of the striatum has been found in functional dyspepsia patients compared to HCs [25]. Only two studies to date have been published using graph analysis on structural brain MRI data in IBS [17,26]: one using binary graphs of regional gray matter volume comparing IBS to HCs [17], and one using weighted graphs of diffusion weighted imaging to study connectivity comparing patients with ulcerative colitis, IBS and HCs [26].…”
Section: Introductionmentioning
confidence: 99%